2021
DOI: 10.18332/tid/140824
|View full text |Cite|
|
Sign up to set email alerts
|

Association of heated tobacco product use and secondhand smoke exposure with suicidal ideation, suicide plans and suicide attempts among Korean adolescents: A 2019 national survey

Abstract: a death rate of 9.1 per 100000 in 2018 2 . Korean adolescents (in 2019) faced suicide thoughts (13.1%), had suicide plans (4%), and suicide attempts (3%) 3 . According to one study, 33.4% of people who think about suicide planned suicide, and 33.9% of those who think about suicide try to commit suicide 4 .Several studies have reported an association between smoking and suicidal behaviors in adolescents [5][6][7] and conventional and e-cigarette consumption and exposure to SHS have been ABSTRACT INTRODUCTION T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In recent years, e-cigarettes, vapes, and flavored nicotine products have gained wide popularity, in part because they are often marketed as safe alternatives to conventional cigarettes. 18 , 33 , 34 However, several nationwide surveys have reported an increased risk of SAs among middle school and high school students with a lifetime use of e-cigarettes 16 , 35 , 36 and vaping devices. 37 , 38 , 39 , 40 Additional work suggests that the association between smoking and SAs may be largest for smoking initiation, 41 which is consistent with the relatively early developmental patterns observed in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, e-cigarettes, vapes, and flavored nicotine products have gained wide popularity, in part because they are often marketed as safe alternatives to conventional cigarettes. 18 , 33 , 34 However, several nationwide surveys have reported an increased risk of SAs among middle school and high school students with a lifetime use of e-cigarettes 16 , 35 , 36 and vaping devices. 37 , 38 , 39 , 40 Additional work suggests that the association between smoking and SAs may be largest for smoking initiation, 41 which is consistent with the relatively early developmental patterns observed in the present work.…”
Section: Discussionmentioning
confidence: 99%
“…There is ongoing controversy regarding whether smoking increases the risk of depression (6,15) or not (16)(17)(18)(19). The present study first examined the association between smoking status and depression by analyzing data in the NHANES database (2005-2018).…”
Section: Discussionmentioning
confidence: 99%
“…One study defined suicidal ideation as a broad term used to describe a range of contemplations/wishes/preoccupations related to death/suicide [16]. Moreover, some studies include the construct of suicide planning within the notion of suicidal ideation, while others do not [17]. Research has shown that suicide prevention for older adults is challenging due to fewer warning signs and the greater use of deadlier methods [16].…”
Section: Is Thriving In Life Related To Quality Of Life and Suicidal ...mentioning
confidence: 99%